MONITORING AND EVALUATION OF TEACHER EFFECTIVENESS , A CASE OF TEACHER PERFORMANCE APPRAISAL AND DEVELOPMENT TOOL IN PUBLIC SECONDARY SCHOOLS IN NYANDARUA SOUTH SUB- COUNTY, KENYA - Ibrahim, Khatete (Advances in Social Sciences Research Journal, 2020)
Abstract The purpose of this study was to investigate the monitoring and evaluation of teacher effectiveness a case of Teacher Performance Appraisal and Development tool (TPAD) in public secondary schools in Nyandarua South Sub-county, Nyandarua County, Kenya. The study was set to achieve three objectives; To determine the influence of teacher clog in and clog out exercise on teacher performance in public secondary schools in Nyandarua South Sub-county, Nyandarua county Kenya, to examine the influence of teachers’ class registers on teacher performance in public secondary schools and to determine the influence of teachers adherence to school deadlines on their performance in public secondary schools. The study was guided by Performance Appraisal Model and benefited from descriptive survey research design. The target population was all 18 public secondary schools in Nyandarua south sub-county. The respondents were 18 Principals, 18 deputy Principals 20 H.O.D s and 90 teachers being a sample size of 30 percent of the entire public school population. Teachers were sampled using simple random sampling to obtain five teachers in every sampled school, totaling to 90 teachers. Questionnaires, interview guide and document analysis guide formed the instruments used for data collection. Descriptive statistics was used to analyze collected data. The study findings revealed that monitoring of teachers on their reporting on duty and leaving from duty improved the teachers stayed in school hence more contact time between teachers and learners in school, the monitoring of teacher class attendance improved teachers’ syllabus coverage. A majority of the schools are completing the syllabus coverage in time. The teachers are now able to do revision as they prepare students for examinations and promotion to the next grades. The meeting of deadlines has created a positive culture among the teachers in the schools. The teachers now look at meeting the deadlines set by the schools as a good thing that is making them more responsible. Lastly the strategies being used to monitor teachers attendance on their duties has resulted into impressive performance of teacher in their duties. Based on the findings and Conclusions of the study, it is recommended that TPAD tool for monitoring teachers on time management should be emphasized. The practice should be borrowed and applied to other areas of school operations.